BUDDHIST PSYCHOLOGICAL FACTORS AFFECTING THE HAPPINESS IN LEARNING OF PRIMARY SCHOOL STUDENTS IN BUENG NGAM SUBDISTRICT, NONG PHOK DISTRICT, ROI ET PROVINCE - Hirunsiraya , Phachiraya; Aphipanyo , PhrapaladSoravit; Wachirapanyo, PhrasomutChokdee; Mererk, Sayyud (Journal of Educational Review Faculty of Education in MCU, 2026)
This research article aims to: 1) study the level of Buddhist psychological factors and happiness in learning among primary school students in Bueng Ngam Subdistrict, Nong Phok District, Roi Et Province; and 2) compare students’ happiness in learning classified by gender and family status. This research is a quantitative research using questionnaires to collect data from a sample of 152 primary school students, comprising 80 students from Nong Khae Dong School and 72 from Nong Waeng Bueng Ngam School. Data were analyzed using basic statistics, namely mean, standard deviation, and statistical tests. The research results found that: 1) Overall levels of Buddhist psychological factors and happiness in learning: (1) The happiness in learning among primary school students in Bueng Ngam Subdistrict was found to be at a high level overall. When considering individual dimensions, all three aspects were also rated at a high level. When ranked by dimensions, it was found to be at a high level in all three aspects: positive feelings toward others, positive feelings toward oneself in learning, and positive feelings toward the subject being studied, respectively. (2) The level of Buddhist psychological factors of primary school students in schools in Bueng Ngam Subdistrict, Nong Phok District, Roi Et Province, was at a high level overall. These were ranked as follows: (1) Chanda (aspiration and satisfaction in learning), (2) Viriya (diligence and effort), (3) Citta (attentiveness and active thought), and (4) Vimams (reflection and analytical reasoning), respectively. 2) The comparative analysis of learning happiness and the Buddhist psychological factors affecting it among primary school students in Bueng Ngam Subdistrict, Nong Phok District, Roi Et Province, categorized by gender, educational level, and family status, showed no statistically significant differences at the 0.05 level overall.